An In Vitro Model for Oral Mixed Biofilms of Candida albicans and Streptococcus gordonii in Synthetic Saliva - Montelongo-Jauregui, Daniel; Srinivasan, Anand; Ramasubramanian, Anand K.; Lopez-Ribot, Jose L. (Frontiers in Microbiology, 2016)
As a member of the normal human oral microbiota, the fungus C. albicans is often found in association with Streptococcus gordonii, a member of dental plaque forming bacteria. Evidence suggests that S. gordonii serves as a facilitator of C. albicans adherence to dental tissues, which represents a clinically relevant problem, particularly for immunocompromised individuals that could subsequently develop fungal infections. In this study we describe the development of a relatively simple and economical in vitro model that allows for the growth of mixed bacterial/fungal biofilms in 96-well microtiter plates. We have applied this method to test and compare the growth characteristics of single and dual species biofilms in traditional microbiological media versus a synthetic saliva medium (basal medium mucin, BMM) that more closely resembles physiological conditions within the oral cavity. Results indicated a synergistic effect for the formation of biofilms when both microorganisms were seeded together under all conditions tested. The structural and architectural features of the resulting biofilms were further characterized using scanning electron microscopy (SEM) and confocal scanning laser microscopy (CSLM). We also performed drug susceptibility assays against single and mixed species biofilms using commonly used antifungals and antibacterial antibiotics, both in monotherapy and in combination therapy, for a direct comparison of resistance against antimicrobial treatment. As expected, mixed species biofilms displayed higher levels of resistance to antimicrobial treatment at every dose tested in both traditional media and BMM synthetic saliva, as compared to single-species biofilms.